2021
DOI: 10.21203/rs.3.rs-725749/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symmetry Breaking of PT-symmetric Solitons in Self-defocusing Saturable Nonlinear Schrödinger Equation

Abstract: The symmetry breaking phenomenon of the parity-time (PT) symmetric solitons in self-defocusing saturable nonlinear Schrödinger equation is studied. As the soliton power increases, branches of asymmetric solitons are separated from antisymmetric solitons, and they coexist with both symmetric and antisymmetric solitons. The anti-symmetric solitons require different power thresholds when they are under different saturable nonlinear strength. The stronger the saturable nonlinearity is, the larger the power thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This high response rate demonstrates the unique advantages of montmorillonite powder in hemostasis, bringing a significant clinical benefit to patients. Besides its remarkable efficacy, MST has fewer adverse effects [9]. No significant drug side effects or toxic effects were found in clinical trials and practical applications [10].…”
Section: Efficacy Evaluation Indexmentioning
confidence: 99%
“…This high response rate demonstrates the unique advantages of montmorillonite powder in hemostasis, bringing a significant clinical benefit to patients. Besides its remarkable efficacy, MST has fewer adverse effects [9]. No significant drug side effects or toxic effects were found in clinical trials and practical applications [10].…”
Section: Efficacy Evaluation Indexmentioning
confidence: 99%
“…As is well known, linear spectra of the PT -symmetric systems remain purely real due to the exact balance between the gain and loss, provided that the strength of the gain-loss distribution does not exceed a certain critical value [20][21][22][23][24][25][26][27]. And a multitude of intensive research results on PTsymmetric systems have been reported [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Experimentally, setups demonstrating persistent PT symmetry were realized in optics [23,44,45].…”
Section: Introductionmentioning
confidence: 99%